An Analysis of Students Errors in Direct-Indirect Sentence in Online Learning during Covid-19 Pandemic of Tenth Grade Vocation High School: Analisis Kesalahan Siswa pada Kalimat Langsung Tidak Langsung dalam Pembelajaran Online pada Pandemi Covid-19 Kelas 10 SMK - Aruma Dwi Cindani; Niko Fediyanto (Academia Open, 2022)
This research refers to the phenomenon that occurs in the world of education in a pandemic situation. The author uses the object of research in class X-Banking students in the second semester of SMK Yapalis Krian for the academic year 2021/2022. The research sample was taken through the data of individual student assignments using the purposive sumpling method to select the object to be studied. In addition, students who will be studied tend to have low interest in participating in online learning. The purpose of this study was to obtain clear information about students' errors in learning Direct and Indirect speech in the sentence using qualitative descriptive methods. At the data collection stage, the author uses data triangulation methods such as observation checklists, documentation and open-ended interviews.The results showed that students made mistakes by being influenced by two factors that students tended to experience during direct and indirect learning, namely the lack of student interest in learning methods. This results in students often not participating in online learning. Furthermore, the most common errors found in students are grammatical errors. With > 8 students who have difficulty due to lack of mastery of grammar correctly.